An outcome evaluation of the Methodist Home for Children’s value-based therapeutic environment model - Strom, Kevin J. (Journal of experimental criminology, 2017)
This study presents an outcome evaluation of the Value-Based Therapeutic Environment model, a multipurpose, cognitive-behavioral treatment approach for juvenile offenders.